PENERAPAN ADMINISTRASI TRANSAKSI BISNIS PADA USAHA RUMAHAN (HOME INDUSTRI) PENGRAJIN TENUN SONGKET TRADISIONAL DI DUSUN TANGKEP LOMBOK TENGAH - Basuki Srihermanto; Siti Yulianah M. Yusuf; Iswan, Iswan (Juremi: Jurnal Riset Ekonomi, 2026)
Efforts to improve the economy can include strengthening the position and skills of traditional home-based businesses. Traditional songket weaving artisans have grown and developed rapidly and are able to support the tourism industry. Various government efforts have been undertaken to stimulate the success of home industries, including providing business capital assistance. Therefore, entrepreneurs must be prepared with the necessary credit instruments. One such instrument is the maintenance of business administration records. The purpose of this study was to analyze and identify traditional songket weaving artisans in Tangkep Hamlet, Central Lombok, who have recorded their business transactions and those who have not. This study was conducted in the traditional weaving craft industry in Tangkep Hamlet, Central Lombok. A survey method was used on a sample. Data collection techniques included questionnaires, observation, and interviews. The results showed that almost all samples showed no record keeping of business transactions; even if they did, they were very rudimentary and far from the applicable business transaction recording standards. From this research, it is hoped that it can provide information for stakeholders to be able to pay attention to traditional songket weaving craftsmen in Tangkep Hamlet, Central Lombok for the advancement of the business world and tourism in Indonesia.